2016 Resilience Week (RWS) 2016
DOI: 10.1109/rweek.2016.7573320
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of fixed-time control of signalized intersections to cyber-tampering

Abstract: Recent experimental studies have shown that traffic management systems are vulnerable to cyber-attacks on sensor data. This paper studies the vulnerability of fixedtime control of signalized intersections when sensors measuring traffic flow information are compromised and perturbed by an adversary. The problems are formulated by considering three malicious objectives: 1) worst-case network accumulation, which aims to destabilize the overall network as much as possible;2) worst-case lane accumulation, which aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Laszka et al performed a theoretical analysis to estimate the potential congestion an attacker can create assuming that she can arbitrarily compromise multiple signal controllers [30]. A follow-up study was then performed for the same attack goal but with a weak assumption, in which the attacker can only compromise the sensors that collects traffic flow information [26]. In comparison, neither of these work analyzes the CV-based signal control scenario targeted in our work.…”
Section: Related Workmentioning
confidence: 99%
“…Laszka et al performed a theoretical analysis to estimate the potential congestion an attacker can create assuming that she can arbitrarily compromise multiple signal controllers [30]. A follow-up study was then performed for the same attack goal but with a weak assumption, in which the attacker can only compromise the sensors that collects traffic flow information [26]. In comparison, neither of these work analyzes the CV-based signal control scenario targeted in our work.…”
Section: Related Workmentioning
confidence: 99%
“…For these two movements, the connector capacity constraints are given by y t ij ≤ Q ij α t ij and y t pq ≤ Q pq α t pq . For the case where both (i, j) and (p, q) have the same (single-lane) flow capacity: Q ij = Q pq = 1 vehicle per t, these constraints can alternatively be written as y t ij + y t pq ≤ 1 (10) and y t ij , y t pq ∈ {0, 1}. In order to represent this graphically, we introduce two transshipment nodes, u and v as depicted in Fig.…”
Section: ) Intersection Conflicting Movementsmentioning
confidence: 99%
“…Works ( Ghena et al, 2014;Cerrudo, 2015 ) have demonstrated that networked traffic systems are vulnerable to a variety of cyber attacks. Other works ( Ghafouri et al, 2016;Laszka et al, 2016;Reilly et al, 1755;Chen et al, 2018;Shoukry et al, 2018 ) attempt to quantify cyber-physical impacts of traffic control cyber-attacks and also attempt to solve for optimal attacks. Shoukry et al (2018) also tries to design a traffic network that is resilient to Sybil (fake car) attacks.…”
Section: Motivationmentioning
confidence: 99%
“…To model similar attacks to the one in the motivational example, related works ( Chen et al, 2018;Ghafouri et al, 2016;Laszka et al, 2016 ) have implemented existing traffic network and behavior models such as the Cell Transmission Model (CTM) ( Daganzo, 1995 ) and the single queue model-based network model ( Varaiya, 2013 ). Still, most of these models contain limited analytical properties, miss certain behaviors, and are challenging to use for larger grid networks (e.g., Manhattan grid networks).…”
Section: Research Challenges and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation